2010
DOI: 10.5194/npg-17-169-2010
|View full text |Cite
|
Sign up to set email alerts
|

Record-breaking earthquake intervals in a global catalogue and an aftershock sequence

Abstract: Abstract. For the purposes of this study, an interval is the elapsed time between two earthquakes in a designated region; the minimum magnitude for the earthquakes is prescribed. A record-breaking interval is one that is longer (or shorter) than preceding intervals; a starting time must be specified. We consider global earthquakes with magnitudes greater than 5.5 and show that the record-breaking intervals are well estimated by a Poissonian (random) theory. We also consider the aftershocks of the 2004 Parkfiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…This idea was extended to earthquakes by Ref. [16] where the sequence of interval times between successive earthquakes were analyzed. It was shown that for global earthquakes the statistics of both record-breaking longer and record-breaking shorter intervals is consistent with IID processes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This idea was extended to earthquakes by Ref. [16] where the sequence of interval times between successive earthquakes were analyzed. It was shown that for global earthquakes the statistics of both record-breaking longer and record-breaking shorter intervals is consistent with IID processes.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time the ratio r of the number of record-breaking longer and shorter intervals proved to be predominantly greater than one, which was suggested as a measure to distinguish between background seismicity and aftershock sequences [16]. Extending the calculation of the ratio r to a broader spatiotemporal interval, before and after the main shock, r < 1 and r > 1 were found, respectively, which addressed a possibility of using record-breaking statistics for forecasting [16]. For interevent times of aftershocks the Omori-type relaxation was proved to be responsible for the power-law increase of the number of records, while in our case the monotonically increasing average event size towards failure plays a similar role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations